A Collaborative Problem-Solving Approach to Improving District Attendance Policy. Issue 6 (September 2022) - Lenhoff, Sarah Winchell; Edwards, Erica B.; Claiborne, Joi; Singer, Jeremy; French, Kate Rollert
Collaborative problem-solving research approaches have the potential to support improvement in educational policy and practice beyond instruction, by facilitating the development of a shared understanding of complex problems and creating social structures where district, community, and research partners can work together to solve them. This study investigates how findings from a developmental evaluation of a district attendance initiative were incorporated into the initiation process of a networked improvement community to create a shared narrative about how members conceptualized the problem of absenteeism and how they should adapt their levers to better align to that problem. The developmental learning process created an infrastructure within which district leaders and community partners could develop a partnership culture that facilitated change in policy. This study suggests the need to revisit the assumptions that have driven non-instructional improvement efforts and highlights the potential of collaborative problem-solving to strengthen the implementation of district reforms.